Models of Teaching Foreign Languages to Young Children - Rodríguez López, Beatriz; Varela Méndez, Raquel (Didáctica. Lengua y Literatura, 2004)
This article deals with young children’s foreign language acquisition and learning within the scope of the very early stages of the school system. Although there are many unorganized theories, opinions, models, and proposals about how to teach modern languages to young children, we will be focusing on the work of researches who have significantly contributed to this area of investigation.